A Model for Consultation Training in Canadian Counsellor Education Programst - Carr, Rey A. (Canadian Journal of Counselling and Psychotherapy, 2012)
A growing awareness exists among school counsellors and counsellor educators that traditional counselling practices have been inadequate for managing the variety of problems and demands for service confronting them. The consultation role has been abundantly proposed and described as an effective way for counsellors to improve their service, prevent problems, focus on student growth and development and be accountable. However, the availability of training programs or descriptions of training resources are virtually nonexistent in Canada, leaving school counsellors without the means to achieve role implementation. Role modelling, research activities, direct-service orientations, conceptual problems and lack of training models are discussed in terms of barriers to the advancement of consultation training. Recommendations for a training model are presented emphasizing specialized training for persons to become consultants to counsellors.